Communication and interpersonal skills enhancement in midwifery: review - Zuzana Škodová (University of Ostrava, 2016)
Aim: The aim of this study is to analyze the available research evidence on the effectiveness of training methods used in communication and interpersonal skills enhancement in midwifery practice and study. Design: Review. Methods: A systematic search in SCOPUS and PubMed databases was performed, with the following selection criteria for studies: quantitative studies in English between the years 2006-2016, using the key words: communication enhancement, communication training, and midwifery in their abstract or title. Theoretical analyses of the problem and review articles were excluded. The search process resulted in the discovery of nine studies focusing on communication skills enhancement in midwifery. Results: All of the available studies confirmed positive effects on communication skills in general, particularly on self-confidence, self-awareness, subjective feelings of competency, and communication within the team. Roleplay with patient-actors proved to be more effective than patient simulators. Conclusion: Although positive effects of the communication training programs were reported in the articles reviewed, there was a high level of heterogeneity in the intervention methods, length and outcome measures used within the training programs. Research studies comparing the effectiveness of the different training methods, using objective outcome measures, and with good quality methodological background, are needed in this area in order to formulate clear recommendations for practice regarding effective interventions.